2017
DOI: 10.14203/ann.bogor.2017.v21.n1.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction and Purification of Soluble Recombinant Human Granulocyte Colony Stimulating Factor in <i>Escherichia coli</i> Using Thioredoxin as Fusion

Abstract: Recombinant human Granulocyte Colony Stimulating Factor (G-CSF) has been produced in a soluble form in Escherichia coli BL21 (DE3) as a fusion protein. The open reading frame of G-CSF was synthetically constructed in previous work and was codon optimized for best expression in E. coli. In this research, the gene was fused to thioredoxin (Trx) at the N-terminal in pET32 vector. The purpose of this research was to optimize the overproduction and purification processes to obtain high yield recombinant protein in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, purification of rhG-CSF from Trx is high cost and low-yielding. [14][15][16][17] Therefore, in this study, rhG-CSF was expressed as insoluble protein without Trx-fusion and found abundantly in inclusion body agregates which are caused by misfolded protein. The inclusion body was then solubilized and purified to obtain active rhG-CSF.…”
Section: Introductionmentioning
confidence: 99%
“…However, purification of rhG-CSF from Trx is high cost and low-yielding. [14][15][16][17] Therefore, in this study, rhG-CSF was expressed as insoluble protein without Trx-fusion and found abundantly in inclusion body agregates which are caused by misfolded protein. The inclusion body was then solubilized and purified to obtain active rhG-CSF.…”
Section: Introductionmentioning
confidence: 99%